If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11e = 9e + 14 Reorder the terms: 11e = 14 + 9e Solving 11e = 14 + 9e Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-9e' to each side of the equation. 11e + -9e = 14 + 9e + -9e Combine like terms: 11e + -9e = 2e 2e = 14 + 9e + -9e Combine like terms: 9e + -9e = 0 2e = 14 + 0 2e = 14 Divide each side by '2'. e = 7 Simplifying e = 7
| 3(x+13)-15=4(x-2)-9 | | 2y+5=y+4 | | 7-3n=8n-4 | | 4x^2+24x-8=0 | | 3d-8=-6+d | | 7(7-3u)=u-11 | | -4(3+f)+6f=-24 | | 5x-12=16-2x | | 15-a=3 | | 6n=4n+20 | | 8p^2+2p+4=0 | | 5x+6=-24 | | -2x-5=-x+1 | | (m-13)(m+6)=m-13 | | 2x+2=108 | | 6(x+8y)= | | t(9+t)=4(2t+5) | | d=jm | | -2x+20=28 | | 8-5a=3a | | 11=15t+16 | | 81s^2+72s=-16 | | x+66=2x-8 | | 9y-7.2=4.5 | | 10t^2-8t-20=0 | | X(3x-10)=7 | | 9-1x=7 | | 4(3x-5)+4(x+2)=20 | | v(v-7)=8 | | 2p+6=8 | | 17=8c-7 | | 4x^2-84x+416=0 |